2016
DOI: 10.1007/s40243-016-0078-9
|View full text |Cite
|
Sign up to set email alerts
|

First-principles molecular dynamics simulations of proton diffusion in cubic BaZrO $$_3$$ 3 perovskite under strain conditions

Abstract: First-principles molecular dynamics simulations have been employed to analyse the proton diffusion in cubic BaZrO 3 perovskite at 1300 K. A non-linear effect on the proton diffusion coefficient arising from an applied isometric strain up to 2 % of the lattice parameter, and an evident enhancement of proton diffusion under compressive conditions have been observed. The structural and electronic properties of BaZrO 3 are analysed from Density Functional Theory calculations, and after an analysis of the electroni… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 42 publications
1
12
0
Order By: Relevance
“…Car‐Parrinello molecular dynamics, as implemented in the cp.x program of the Quantum‐ESPRESSO distribution, was used to perform efficient density‐functional theory simulations using the PBE exchange‐correlation functional. Norm‐conserving pseudopotentials from the extensively tested SSSP library were used, with a planewave cutoff of 70 Ryd.…”
Section: Methodsmentioning
confidence: 99%
“…Car‐Parrinello molecular dynamics, as implemented in the cp.x program of the Quantum‐ESPRESSO distribution, was used to perform efficient density‐functional theory simulations using the PBE exchange‐correlation functional. Norm‐conserving pseudopotentials from the extensively tested SSSP library were used, with a planewave cutoff of 70 Ryd.…”
Section: Methodsmentioning
confidence: 99%
“… 19 21 More recently, Fronzi et al applied DFT-MD simulations on proton conduction in undoped BaZrO 3 and reported that proton diffusion is enhanced when compressive strain is applied on the structure. 22 The authors interpret this increase in diffusion to the shorter O–O distances observed in the compressed material. The effect of strain on proton diffusion has also been demonstrated in Y-doped BaZrO 3 for two dopant concentrations (1% and 12.5%) using MD simulations with a reactive force field based on an Empirical Valence Bond description.…”
Section: Introductionmentioning
confidence: 97%
“…Plane-wave based DFT calculation demonstrate that the proton diffusion coe cient is affected by applied strain in ABO 3 perovskite structure [223], and the enhanced proton diffusion is explained by the formation of preferable proton transport path due to compressive strain in the structure. To analyze the proton diffusion mechanism in the cubic perovskite structure at high temperature, rst-principles MD simulation was performed, which showed that proton diffusion could be enhanced under the application of compressive condition due to the formation of preferential diffusion path (which can be attributed to charge redistribution under this condition).…”
Section: Theoretical Studies On Bzo Proton Conductormentioning
confidence: 97%
“…Induced charge density due to the proton's introduction can be visualized by Fig. 9, which shows that there could be a signi cant difference between the charge distribution of stoichiometric and protonated bulk [223]. However, ab initio MD simulation on a hydrated sample of BZO shows that it is possible for overlapping INS spectra of protons to exist in the local structural environment, clari ed by O-H bend, O-H stretch, and higher-order transitions.…”
Section: Studiesmentioning
confidence: 99%
See 1 more Smart Citation